2018
DOI: 10.3390/f9030117
|View full text |Cite
|
Sign up to set email alerts
|

Pine Plantations and Invasion Alter Fuel Structure and Potential Fire Behavior in a Patagonian Forest-Steppe Ecotone

Abstract: Abstract:Planted and invading non-native plant species can alter fire regimes through changes in fuel loads and in the structure and continuity of fuels, potentially modifying the flammability of native plant communities. Such changes are not easily predicted and deserve system-specific studies. In several regions of the southern hemisphere, exotic pines have been extensively planted in native treeless areas for forestry purposes and have subsequently invaded the native environments. However, studies evaluatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 51 publications
0
28
0
1
Order By: Relevance
“…High threshold impacts occur when impacts ensue only once a critical density or biomass is reached (Figure c). For example, young or low‐density pine invasions do not significantly alter wildfire fuel loads; however, in older or denser invasions, fuel loads and fuel spatial continuity increase rapidly (Figure c, where there is a strong increase in total fuel in older invasions), which can result in altered fire behaviour and fire effects (Davis, Maxwell, Caplat, Pauchard, & Nuñez, ; Paritsis et al, ). High threshold impacts may also occur with litter accumulation, where large amounts of litter bury native vegetation (Brewer, Souza, Callaway, & Durigan, ).…”
Section: Context Dependencementioning
confidence: 99%
“…High threshold impacts occur when impacts ensue only once a critical density or biomass is reached (Figure c). For example, young or low‐density pine invasions do not significantly alter wildfire fuel loads; however, in older or denser invasions, fuel loads and fuel spatial continuity increase rapidly (Figure c, where there is a strong increase in total fuel in older invasions), which can result in altered fire behaviour and fire effects (Davis, Maxwell, Caplat, Pauchard, & Nuñez, ; Paritsis et al, ). High threshold impacts may also occur with litter accumulation, where large amounts of litter bury native vegetation (Brewer, Souza, Callaway, & Durigan, ).…”
Section: Context Dependencementioning
confidence: 99%
“…These ranges are consistent with previous research, which reported pine plantations between 765 and 950 m (Paritsis et al . ). The high topographic relief in Chile creates strong temperature and moisture gradients which likely limit plant growth at high elevation (Veblen et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Paritsis et al . ). Pines require substantially more water than vegetation that undergoes seasonal dormancy and thus can reduce water availability (Le Maitre et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Paritsis et al . ). While many historical and recent large fires in Chile occurred just north of the CTRF region in the more Mediterranean central valley, there are plantations of Eucalypts in the SPCTR as far south as 42 0 on Isla Chiloé, and at the Patagonian dry forest/steppe ecotone lodgepole pine ( Pinus contorta var.…”
Section: The Expansion Of Firementioning
confidence: 97%